Polarisasi Politik dalam Pemilu 2024: Pro dan Kontra Prabowo sebagai Presiden dalam bayang-bayang 1997/1998 - Seraphim Virgine Tadja; M. Asif Nur Fauzi (Sapientia Humana: Jurnal Sosial Humaniora, 2025)
Indonesia’s 2024 presidential election marks a critical juncture in the country’s democratic development, characterized by increasing political polarization. Prabowo Subianto’s renewed candidacy has triggered intense public debate between supporters and critics. This polarization stems not only from ideological and political identity differences but is also reinforced by social media dynamics and lingering public memory of the 1997/1998 reform era, where Prabowo remains a controversial figure. This paper aims to analyze the causes of political polarization in the context of Prabowo’s candidacy, evaluate the arguments for and against him, and examine how historical narratives shape public perception. Employing a qualitative-descriptive method through literature review, the study finds that issues of human rights, militaristic leadership style, and political communication strategies significantly shape public opinion. While some reject Prabowo due to unresolved historical trauma, others see his transformation and leadership experience as valuable assets. This study concludes that political education and neutral media play a vital role in mitigating polarization and reinforcing the foundations of democracy.